2012
DOI: 10.3164/jcbn.11-70
|View full text |Cite
|
Sign up to set email alerts
|

Metal nanoparticle-induced micronuclei and oxidative DNA damage in mice

Abstract: Several mechanisms regarding the adverse health effects of nanomaterials have been proposed. Among them, oxidative stress is considered to be one of the most important. Many in vitro studies have shown that nanoparticles generate reactive oxygen species, deplete endogenous antioxidants, alter mitochondrial function and produce oxidative damage in DNA. 8-Hydroxy-2'-deoxyguanosine is a major type of oxidative DNA damage, and is often analyzed as a marker of oxidative stress in human and animal studies. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 39 publications
2
81
1
6
Order By: Relevance
“…Cerium nitrate hexahydrate (Ce(NO 3 ) 3 ·6H 2 O, 99.9%, SigmaAldrich, St Louis, MO, USA), glycine (NH 2 ·CH 2 COOH, Fisher Scientific, Mumbai, India), chloroauric acid (HAuCl 4 , Loba Chemie, Mumbai, India), and sodium borohydride (NaBH 4 , Sigma-Aldrich) were used for synthesis of both CeO 2 and Au-impregnated CeO 2 nanoparticles.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…Cerium nitrate hexahydrate (Ce(NO 3 ) 3 ·6H 2 O, 99.9%, SigmaAldrich, St Louis, MO, USA), glycine (NH 2 ·CH 2 COOH, Fisher Scientific, Mumbai, India), chloroauric acid (HAuCl 4 , Loba Chemie, Mumbai, India), and sodium borohydride (NaBH 4 , Sigma-Aldrich) were used for synthesis of both CeO 2 and Au-impregnated CeO 2 nanoparticles.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…[3][4][5][6] In vivo studies also reported the potential genotoxic risk of CuO NPs, such as increased neoplastic lesions, point mutations, DNA alterations, and DNA strand breaks. 7,8 Some CuO NPs eventually enter the aquatic systems, raising concerns about toxicity from aqueous exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly the metal based NPs like Ag NPs [19], Au NPs [30] and TiO2 NPs [22] are important for that kind of ROS production and genetic damage. As a result of DNA damage induced by NPs, single-strand DNA breaks, doublestrand breaks, DNA deletions and genomic instability in the form of increase in 8-hydroxy-2-deoxyguanosine levels are formed [50]. According to Mroz et al [ 51] long-term exposure of cells to NPs displayed genome instability under comet assay analysis, altered cell cycle kinetics in flow cytometry and induced protein expression of p53, having a critical role in responding to various stresses that cause DNA damage, and DNA repair-related proteins.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Fen Song et al [50] analyzed the induction of reticulocyte micronuclei and oxidative DNA damage in ICR female mice after intraperitoneal injection of metal oxides (CuO, Fe2O3, Fe3O4, TiO2) and Ag NPs at various doses (0, 1, 3 mg/mouse). The results of the micronucleus assay demonstrated significant increases in micronucleated reticulocyte formation after the intraperitoneal administration of CuO, Fe2O3, Fe3O4, TiO2 and Ag NPs.…”
Section: Genotoxicitymentioning
confidence: 99%